ECONOMIC MANAGEMENT FROM THE PERSPECTIVE OF SCIENTIFIC AND DIGITAL LABOR ORGANIZATIONS - E. A. Khalimon; A. G. Geokchakyan (Вестник университета)
The article presents the results of research on such problems of Economics and Management as scientific and digital labor organizations. The paper describes the need to create artificial intelligence, the stages of the scientific component of labor organization, and the features of the joint use of natural and artificial intelligence in the work and management of human resources, both at the level of public administration and in organizations. The authors pay special attention to the issue of human capital development, as one of the three strategically important areas implemented by the Government of the Russian Federation within the framework of national projects, as well as give a comparative analysis of the indicators of the human capital development index in various countries of the world.